2011
DOI: 10.1245/s10434-011-1751-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Morcellation During Surgery on the Outcomes of Patients with Apparently Early Low-Grade Endometrial Stromal Sarcoma of the Uterus

Abstract: Inadvertent tumor morcellation during surgery has an adverse impact on the outcomes of patients with early LGESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 35 publications
5
69
0
1
Order By: Relevance
“…23 Indeed, the incidence of uterine sarcoma is rare, and leiomyosarcoma accounts for only 30% of all uterine sarcomas. 10 In 2009, Park et al 10,11 found that tumor morcellation was associated with higher abdominopelvic recurrence and decreased disease-free survival for both leiomyosarcoma and endometrial stromal sarcoma but only with decreased survival for leiomyosarcoma. In our study, there were 6 patients who underwent morcellation and who were subsequently diagnosed with uterine sarcoma, either immediately or several years later.…”
Section: Ajogorgmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Indeed, the incidence of uterine sarcoma is rare, and leiomyosarcoma accounts for only 30% of all uterine sarcomas. 10 In 2009, Park et al 10,11 found that tumor morcellation was associated with higher abdominopelvic recurrence and decreased disease-free survival for both leiomyosarcoma and endometrial stromal sarcoma but only with decreased survival for leiomyosarcoma. In our study, there were 6 patients who underwent morcellation and who were subsequently diagnosed with uterine sarcoma, either immediately or several years later.…”
Section: Ajogorgmentioning
confidence: 99%
“…8,9 There are no specific symptoms or signs or reliable diagnostic modalities to differentiate benign from malignant uterine tumors before they are morcellated and removed. 10,11 Parasitic myomas are defined as leiomyomas that are not attached to the uterus and are "parasitic" because they receive their blood supply from surrounding organs. 12 They have a reported incidence of 0.12-0.9% after laparoscopic surgery with power morcellation.…”
mentioning
confidence: 99%
“…About 25% to 75% of patients with early ESS have recurrence in the pelvis and abdomen. These recurrences may be caused by inadvertent tumor morcellation during surgery [57]. Park et al [58] found that inadvertent tumor morcellation during surgery had adverse effects on the disease-free survival of patients with early ESS.…”
Section: Primary Surgerymentioning
confidence: 99%
“…Morcellation of unsuspected uterine sarcomas can be associated with spread of disease and decreased survival rates [9][10][11]. The same is true for variants of leiomyomas such as cellular leiomyoma, atypical leiomyoma, and smooth muscle tumors of undetermined malignant potential [12].The definitive diagnosis of these lesions is provided via histology.…”
Section: Discussionmentioning
confidence: 99%